Deformation and Failure Mechanism of Excavation in Clay Subjected to Hydraulic Uplift - Hong, Yi.; Wang, Lizhong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book presents the latest experimental and numerical analysis work in the field of ground deformation and base instability of deep excavations in soft clay subjected to hydraulic uplift. The authors' latest research findings, based on dimensional analyses, well-instrumented full-scale field tests, systematic coupled-consolidation finite element analyses and centrifuge tests are reported. This book shows how to systematically approach a complex geotechnical problem, from identifying existing problems, reviewing literature, to dimensional and numerical analyses, validation through full-scale testing and centrifuge model testing. The methodologies are also introduced as major tools adopted in geotechnical research.
Introduction -- Literature Review -- Field Investigation of a Multi-propped Excavation in Soft Clay -- Numerical Analyses of the Multi-propped Excavation in Soft Clay -- Dimensional Analysis of Excavation in Clay Subjected to Hydraulic Uplift -- Centrifuge Modelling of a Multi-propped Excavation in Clay Destabilised by Hydraulic Uplift -- Finite Element Analyses: Back-analysis and Parametric Study -- Interpretations of Measured and Back-analysed Results of Centrifuge Tests -- Numerical Parametric Study -- Conclusions and Future Work.
Keywords: Engineering geology; Geotechnical engineering; Numerical analysis; Geoengineering; Geotechnical Engineering and Applied Earth Sciences; Numerical Analysis